The Role of the Social Services and Rehabilitation Center for Persons with Social Welfare Problems (PMKS) of the East Java Provincial Social Service in Psychotic Services - Ida, Alma; Riyadh UB, Ahmad (Journal of Social Science, 2024)
This research study is to analyze the role of social service and rehabilitation centers for Persons with Social Welfare Problems (PMKS) of the East Java Provincial Social Service in serving people with psychotics. The approach used in this research is a qualitative descriptive approach, by conducting interviews, documentation and observation. The results of the research obtained show that: First, the Facilitative Role in services is to meet the basic needs of PMKS by meeting the needs of facilities and infrastructure as well as clothing and food needs for PMKS. Second, the role of education in services at the PMKS Center is currently very helpful for PMKS where various programs and training have been provided to improve the welfare of people with social welfare problems (PMKS). Third, the Representational Role in PMKS center services has collaborated with various institutions and agencies to obtain external resources for training to develop the potential of each different person. Fourth, the technical role in the PMKS center is very helpful in assessing needs for developing individual, group and community potential.